2022
DOI: 10.3390/antiox11030485
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Phyllanthus emblica (Amla) Fruit Supplementation Enhances Milk Fatty Acid Profiles and the Antioxidant Capacities of Milk and Blood in Dairy Cows

Abstract: The objective of this study was to investigate the effect of a diet supplemented with fresh amla fruit as a natural feed additive on blood metabolic parameters, milk antioxidant capacity, and milk fatty acid (FA) proportions in lactating dairy cows. Eight ruminally cannulated mid-lactation dairy cows were used in a repeated crossover design. The first group of four cows received total mixed ration (TMR) feed without fresh amla fruit (control group). The remaining four cows sequentially supplemented fresh amla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 78 publications
1
15
0
1
Order By: Relevance
“…Usharani et al [ 42 ] also reported that 250 mg and 500 mg Emblica officinalis capsules twice daily supplementation for humans improved the antioxidant status of type 2 diabetes patients (improved activities of glutathione and reduced MDA level). Fresh Amla fruit supplementation in dairy cows also improved the activity of SOD in blood [ 13 ]. The increased activity of SOD, along with increased activities of CAT and GSH-Px in the PE5 group, in the current study, is important as the balance of the antioxidants is essential for the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usharani et al [ 42 ] also reported that 250 mg and 500 mg Emblica officinalis capsules twice daily supplementation for humans improved the antioxidant status of type 2 diabetes patients (improved activities of glutathione and reduced MDA level). Fresh Amla fruit supplementation in dairy cows also improved the activity of SOD in blood [ 13 ]. The increased activity of SOD, along with increased activities of CAT and GSH-Px in the PE5 group, in the current study, is important as the balance of the antioxidants is essential for the body.…”
Section: Discussionmentioning
confidence: 99%
“…It is a small- to medium-sized deciduous plant known for its essential role in traditional ayurvedic medicine [ 10 ], with the fruit being the most useful part in this regard [ 11 ]. Amla fruit is rich in phytochemical compounds such as phenolics, flavonoids, tannins, saponins, alkaloids, carbohydrates, and organic acids [ 12 , 13 ]. There are variations in the phytochemical contents of Amla fruit extracts reported in different studies, which could be due to the variety, source of the fruit, stage of development during harvest, and methods of collection, processing, and extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Завдяки даним сполукам є можливість передачі нервових імпульсів, енергетичне живлення клітин, синтез певних гормонів і ліпідів, синтез модифікованих білків, запасання енергетичних резервів за допомогою синтезу триацилгліцеридів. Споживаючи поживні субстрати, в організм вивільняється певна кількість вільних жирних кислот (Cheng et al, 2021;Młynek et al, 2021;Tilahun et al, 2022). В кровотоці вони захоплюються білками та надходять у клітину.…”
Section: вступunclassified
“…Particularly in beef cattle and dairy cows, some studies have evaluated the effects of dietary supplementation with FLAs on animal performance ( 19 , 22 ), serum antioxidant status ( 23 , 24 ), rumen fermentation and nutrient digestibility ( 16 , 20 ), meat physicochemical characteristics ( 25 , 26 ) and milk production and composition ( 15 , 27 ). However, the results obtained so far are still inconsistent and controversial, probably due to the wide variability among these studies regarding the experimental periods, the doses, and the type of FLAs used ( 14 ).…”
Section: Introductionmentioning
confidence: 99%